Scientific publications and the curriculum vitae: A medical student's Achilles' heel? - Sathian, Brijesh; Fatima, Huda; Hussain, Syed Ather; Menezes, Ritesh G (Nepal Journal of Epidemiology, 2017)
With the number of hopeful students eager to surge ahead in the noble profession of medicine, increasing every day, the world of both academic as well as clinical medicine is fast becoming more competitive. Thanks to globalization, our world is far more interconnected than it ever was. Discoveries and breakthroughs are occurring right this minute and are being transmitted live the very next. This is an exciting time to be a part of the medical community. There is no limit, no barrier to what a person may achieve, albeit with untiring hard work and an unflagging determination.